An extra year of onco-nephrology fellowship training is not required for the subspecialty. Issue 1 (February 2021) - Anand, Shuchi; Bassil, Claude; Sise, Meghan E
Onconephrology, a new and evolving subspecialty of Nephrology. Several Universities have created onconephrology fellowships affiliated with major cancer centers. The aim of this article is to present and rationale for why a 1-year training program may not be necessary to launch a successful career in onconephrology.